Comparison of Growth Performance of Khari Goats Fed with Different Level of Rice Bran and Urea Treated Rice Straw (UTRS) in Fodder Based Diets - Tiwari, MR; Shrestha, BK; Panday, LN; Mandal, P (Nepal Journal of Science and Technology, 2012)
For correcting, the nutritional imbalance of rice straw feed diet by supplementing energy and protein rich concentrate (rice bran) an experiment was carried out in growing male goats at Agriculture Research Station (Goat), Bandipur, Tanahun from November 2009 to Januwary 2010. Twelve goats of 6-7 months of age and similar body weight were divided into four treatment groups having three animals in each group by using complete randomized design. Four types of diet were formulated for these experimental animals. The animals of control group (treatment 1) were provided UTRS, Raikhanayo and concentrate mixture at the rate of 65, 25 and 10% of dry matter requirement, respectively. Dry matter requirement of treatment 2 was fulfilled by providing urea treated rice straw (UTRS), Raikhanayo and rice bran @ 65, 25 and 10%, respectively. Treatment 3 received dry matter requirement by UTRS, Raikhanayo and rice bran @ 55, 25 and 20%, respectively whereas treatment 4 got @ 45, 25 and 30 percent UTRS, Raikhanayo and rice bran, respectively. The study revealed that there was no significant effect in fodder and UTRS intake between diet groups except rice bran (P<0.001). Likewise, there was highly significant (P<0.001) effect in total dry matter intake between diet groups. The highest body weight gain was observed in treatment 4 (17.5 ± 1.8 kg) followed by treatment 3 and 2 (15.66 ± 1.15 kg and 15.5 ± 3.27 kg, respectively). The lowest body weight gain was noted for treatment 1 (14.5 ± 1.80 kg); however, it was also found non-significant between diet groups. Average daily gain was recorded highest in treatment 4 (50 g /day) followed by treatment 2 (31.44 g /day) whereas average daily gain for treatment 1 and 2 were recorded similar (27.77 g /day). DOI: http://dx.doi.org/10.3126/njst.v12i0.6480 Nepal Journal of Science and Technology 12 (2011) 55-60